CABIN OF AIRCRAFT AS A CONTROL OBJECT ACCORDING TO THE TEMPERATURE OF THE ON-BOARD AIR CONDITIONING SYSTEM - Хлистун, О. І. (Proceedings of National Aviation University, 2021)
The cockpit of the aircraft in the form of two series-connected aperiodic rings of the first order, taking into account the accumulating action of air and equipment in it, and rings of differentiating type are considered. For the cabin as an adjustable object in terms of temperature, the transfer functions for regulating and disturbing actions are obtained.